Application of copper-loaded Ce-MOF derived cerium oxide carbon nanorod composite material in electrocatalytic reduction of Cr (VI)
Through the copper-supported Ce-MOF derived ceria carbon nanorod composite, the problem of insufficient activity and stability of copper-based materials during electrocatalytic reduction of Cr(VI), achieving efficient and stable Cr(VI) reduction, and the material has high copper dispersion and conductivity.
Patent Information
- Application Number
- CN202411997409.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing copper-based materials are insufficient in electrocatalytic reduction of Cr(VI), and the Cu atomic utilization rate is low, which can easily lead to secondary pollution of water.
The copper-loaded Ce-MOF-derived ceria carbon nanorod composite was used to prepare Ce-MOF by hydrothermal method, and the impregnation method was loaded with copper, followed by carbonization reaction to form the Cu-loaded Ce-MOF-derived ceria carbon nanorod composite.
The reduction activity and stability of the copper-based material are improved, the dispersion and conductivity of Cu are enhanced, and the conversion rate and catalytic activity of Cr(VI) are significantly improved, and the material maintains catalytic activity during 10 catalyst reuse cycles.
Smart Images

Figure CN119797517A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic materials, and in particular to application of a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material in electrocatalytic reduction of Cr(VI). Background Art
[0002] Copper-based materials are widely used in the reduction and removal of water pollution as an ideal reducing agent with the characteristics of low cost, high reactivity and environmental friendliness. However, nano-scale metallic copper is very easy to agglomerate and oxidize, which usually leads to reduced current density and electrocatalytic activity. The size of Cu active components is mainly distributed between tens of nanometers and hundreds of microns, and the utilization rate of Cu atoms is low. During the reaction process, the leaching of Cu in the material will also cause secondary pollution to the water body. In addition, the pH value in the reaction system has a great influence on the reduction activity of Cu-based materials.
[0003] At present, researchers have proposed some methods to improve the reduction activity and stability of copper-based materials. Loading nanoscale Cu on oxygen-rich vacancy carriers to form heterojunctions is an effective way to stabilize active Cu and effectively enhance the electron transfer between active sites and reactants. It is worth noting that CeO2 has a strong 3+ and Ce 4+ The flexible valence transitions between oxidation states make CeO2 an attractive catalyst support in various catalysts. In addition, CeO2 is an n-type semiconductor that can provide high electron density, and its surface oxygen vacancies provide abundant anchoring sites to stabilize metal particles through strong metal-support interactions. Similarly, CeO2 with oxygen vacancies, in addition to acting as a co-catalyst, also provides abundant active sites for the adsorption and activation of Cr(VI), thereby connecting with oxygen vacancies and reducing Ce. 3+ Site binding enhances the electrochemical reduction of Cr(VI). However, CeO2 has poor conductivity, which is not conducive to charge transfer in electrocatalytic reactions. Therefore, it is of great significance to study and prepare copper-based materials with high reduction activity and stability and apply them to the reduction reaction of pollutants. Summary of the invention
[0004] The purpose of the present invention is to provide a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material for use in the electrocatalytic reduction of Cr(VI), which can improve the reduction activity and stability of the copper-based material.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an application of a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material in electrocatalytic reduction of Cr(VI). The preparation method of the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material comprises the following steps:
[0007] A cerium precursor, a dispersant, an organic ligand and an organic solvent are mixed and subjected to a hydrothermal reaction to obtain a Ce-MOF material; the organic ligand comprises trimesic acid;
[0008] The Ce-MOF material, the copper source and the impregnation solvent are mixed and loaded to obtain the copper-loaded Ce-MOF;
[0009] The copper-loaded Ce-MOF is subjected to a carbonization reaction in a protective atmosphere to obtain a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material.
[0010] Preferably, the cerium precursor includes cerium nitrate hexahydrate or cerium trichloride heptahydrate; the molar ratio of cerium element to organic ligand in the cerium precursor is 1:1-3.
[0011] Preferably, the dispersant includes polyvinyl pyrrolidone or polyvinyl alcohol; and the molar ratio of the dispersant to the cerium precursor is 1:3-6.
[0012] Preferably, the organic solvent includes at least one of ethanol and N,N-dimethylformamide; the temperature of the hydrothermal reaction is 120-140° C., and the time is 2-12 hours.
[0013] Preferably, the copper source includes copper nitrate trihydrate or copper sulfate pentahydrate; the mass ratio of the copper source to the Ce-MOF material is 4 to 80:100; the load temperature is 25° C., and the time is 0.5 to 1 h.
[0014] Preferably, the temperature of the carbonization reaction is 800-950°C, the time of the carbonization reaction is 0.5-2h; the protective gas used in the protective atmosphere is nitrogen or argon; the flow rate of the protective gas is 25-100 mL min -1 .
[0015] Preferably, in the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material, the loading amount of Cu is 2.4 to 32.1 wt %.
[0016] Preferably, the application method comprises the following steps: after loading the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material on a carbon substrate, using it as a working electrode to perform a reduction reaction on wastewater containing Cr(VI).
[0017] Preferably, the amount of the copper-supported Ce-MOF-derived cerium oxide carbon nanorod composite material on the carbon substrate is 0.5-5 mg / cm 2 The concentration of Cr(VI) in the Cr(VI)-containing wastewater is 4.8-10.2 mg / L.
[0018] Preferably, the reduction reaction temperature is 25° C. and the time is 0.5 to 2 h.
[0019] The present invention provides an application of a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material in the electrocatalytic reduction of Cr(VI), wherein a cerium precursor, an organic ligand and a solvent are mixed, and a hydrothermal polymerization reaction is performed to obtain a Ce-MOF material; the Ce-MOF material is then compounded with copper by an impregnation method, and then a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material is obtained by a carbonization pyrolysis reaction. The cerium oxide derived from Ce-MOF can improve the specific surface area of the composite material, facilitate the exposure of active sites and the diffusion of electrolytes, and improve the electron transfer capacity and dispersibility; coupling CeO2 to MOF-derived carbon to form a CeO2-C composite material can improve conductivity and promote charge transfer; the metal carrier interaction between Cu and CeO2 promotes the Cu+-Ov-Ce 3+ The introduction of CeO2 leads to the formation of Cu-[OX]-Ce structure, which enhances the dispersion of Cu and forms stable electron-rich Cu(I) species, thus being used as electrocatalyst for the electrocatalytic reduction of Cr(VI).
[0020] The present invention can prepare Cu / CeO2@C catalysts with different Cu loadings by changing the amount of copper source. When the Cu loading is as high as 16.2%, the Cu / CeO2@C catalyst still retains a unique porous rod-like structure and high copper dispersibility. In addition, the surface potential of the Cu / CeO2@C catalyst varies with the Cu loading, and the presence of CeO2 is conducive to the adsorption of Cr(VI). Therefore, the Cr(VI) conversion rate of Cu(16.2) / CeO2@C is 95%, and the catalytic activity is 1.55min -1 mg -1 In addition, the electrochemical reduction potential and pH value were adjusted to effectively improve the performance of the catalyst in electrocatalytic reduction of Cr(VI). When the pH value was 2.91 and the applied potential was -1.0 V vs. SCE, the Cr(VI) reduction of Cu / CeO2@C was as high as 98% and the activity was 1.59 min -1 mg -1Moreover, the material can maintain its catalytic activity over 10 catalyst reuse cycles without catalyst deactivation, indicating a very high catalyst stability and showing great potential as an efficient electrocatalyst for the reduction of Cr(VI). BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 X-ray diffraction pattern of Cu / CeO2@C prepared in Examples 1 to 5;
[0022] Figure 2 SEM images of CeO2@C in Comparative Example 1 and Cu / CeO2@C prepared in Examples 1 to 5, wherein (a) is CeO2@C, (b) is Cu(2.4) / CeO2@C, (c) is Cu(3.8) / CeO2@C, (d) is Cu(8.0) / CeO2@C; (e) is Cu(16.2) / CeO2@C; (f) is Cu(32.1) / CeO2@C;
[0023] Figure 3 TEM images of CeO2@C in Comparative Example 1 and Cu / CeO2@C prepared in Examples 1 to 5; wherein (a) is CeO2@C, (b) is Cu(2.4) / CeO2@C, (c) is Cu(3.8) / CeO2@C, (d) is Cu(8.0) / CeO2@C; (e) is Cu(16.2) / CeO2@C; (f) is Cu(32.1) / CeO2@C;
[0024] Figure 4 TEM images of Cu(16.2) / CeO2@C prepared in Example 4, wherein (a) is a 100 nm TEM image, (b) and (c) are 5 nm TEM images, (d) is a 500 nm TEM image, (e) is a Cu element distribution image, and (f) is a Ce element distribution image;
[0025] Figure 5 The reduction performance results of different materials for dichromate ions, where (a) and (c) are the reduction removal curves, and (b) and (d) are the mass activities of Cu in the reaction;
[0026] Figure 6 The reduction performance results of Cu(16.2) / CeO2@C prepared in Example 4 in different potential reaction systems, where (a) is the reduction removal curve and (b) is the mass activity diagram of Cu in the reaction;
[0027] Figure 7 The reduction performance results of Cu(16.2) / CeO2@C prepared in Example 4 in reaction systems with different pH values, where (a) is the reduction removal curve and (b) is the mass activity diagram of Cu in the reaction;
[0028] Figure 8 The cyclic reaction curve of Cu(16.2) / CeO2@C prepared in Example 4 to dichromate ion, where (a) is the reduction removal curve and (b) is the mass activity diagram of Cu in the reaction. DETAILED DESCRIPTION
[0029] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0030] The present invention provides an application of a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material in electrocatalytic reduction of Cr(VI). The preparation method of the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material comprises the following steps:
[0031] A cerium precursor, a dispersant, an organic ligand and an organic solvent are mixed and subjected to a hydrothermal reaction to obtain a Ce-MOF material; the organic ligand comprises trimesic acid;
[0032] The Ce-MOF material, the copper source and the impregnation solvent are mixed and loaded to obtain the copper-loaded Ce-MOF;
[0033] The copper-loaded Ce-MOF is subjected to a carbonization reaction in a protective atmosphere to obtain a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material.
[0034] The present invention mixes a cerium precursor, a dispersant, an organic ligand and an organic solvent, and performs a hydrothermal reaction to obtain a Ce-MOF material.
[0035] In the present invention, the organic ligand includes trimesic acid; the cerium precursor preferably includes cerium nitrate hexahydrate or cerium trichloride heptahydrate; the molar ratio of cerium element to organic ligand in the cerium precursor is preferably 1:1-3, more preferably 1:1-2.
[0036] In the present invention, the dispersant preferably includes polyvinyl pyrrolidone or polyvinyl alcohol; the molar ratio of the dispersant to the cerium precursor is preferably 1:3-6, more preferably 1:4-5.
[0037] In the present invention, the organic solvent preferably includes at least one of ethanol and N,N-dimethylformamide.
[0038] The present invention preferably mixes a cerium precursor, an organic ligand and an organic solvent to obtain a first mixed solution, and mixes a dispersant with the organic solvent to obtain a second mixed solution; then the first mixed solution and the second mixed solution are mixed, stirred for a certain period of time at room temperature, and then a hydrothermal reaction is carried out; the types of organic solvents used in the first mixed solution and the second mixed solution are preferably the same or different, and the amount is preferably adjusted according to demand to ensure that the reaction proceeds smoothly; the stirring time is preferably 5 to 120 minutes, more preferably 10 minutes, 20 minutes, 40 minutes, 50 minutes, 60 minutes, 80 minutes or 100 minutes; the stirring rate is preferably 200 rpm to 800 rpm, more preferably 300 rpm, 400 rpm, 500 rpm, 600 rpm or 700 rpm.
[0039] In the present invention, the temperature of the hydrothermal reaction is preferably 120 to 140° C., more preferably 120 to 130° C., and the time is preferably 2 to 12 h, more preferably 4 to 10 h, and further preferably 6 to 8 h.
[0040] After the hydrothermal reaction is completed, the present invention preferably collects the solid Ce-MOF by filtration, washes it with ethanol and water, and dries it at 60° C. for 4 h to obtain the Ce-MOF material.
[0041] After obtaining the Ce-MOF material, the present invention mixes the Ce-MOF material, a copper source and an impregnation solvent for loading to obtain copper-loaded Ce-MOF.
[0042] In the present invention, the copper source preferably includes copper nitrate trihydrate or copper sulfate pentahydrate; the mass ratio of the copper source to the Ce-MOF material is preferably 4 to 80:100, more preferably 37 to 75:100.
[0043] In the present invention, the impregnation solvent is preferably ethanol. The present invention preferably mixes the copper source with the impregnation solvent, adds the Ce-MOF material, and loads it under stirring conditions. During the stirring process, the impregnation solvent evaporates and the copper-loaded Ce-MOF is collected and recorded as Cu / Ce-MOF.
[0044] In the present invention, the temperature of the load is preferably 25° C., and the time is preferably 0.5 to 1 h.
[0045] After obtaining the copper-loaded Ce-MOF, the present invention performs a carbonization reaction on the copper-loaded Ce-MOF in a protective atmosphere to obtain a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material.
[0046] In the present invention, the temperature of the carbonization reaction is preferably 800-950°C, more preferably 850-900°C; the time of the carbonization reaction is preferably 0.5-2h, specifically preferably 0.5h, 1h, 1.5h, 2h; the protective gas used in the protective atmosphere is preferably nitrogen or argon; the flow rate of the protective gas is preferably 25-100mL min -1 , more preferably 30 to 80 mL / min -1 , more preferably 50-75 mL min -1 During the carbonization process, Ce-MOF is converted into CeO2@C, and copper salt is converted into copper oxide loaded on CeO2@C.
[0047] In the present invention, in the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material, the loading amount of Cu is preferably 2.4 to 32.1 wt %, more preferably 2.4 to 16.2 wt %, and further preferably 3.8 to 8.0 wt %.
[0048] In the present invention, the application method is preferably: after the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material is loaded on a carbon substrate, it is used as a working electrode to perform a reduction reaction on wastewater containing Cr(VI).
[0049] In the present invention, the amount of the copper-supported Ce-MOF-derived cerium oxide carbon nanorod composite material on the carbon substrate is preferably 0.5 to 5 mg / cm 2 , more preferably 1 to 4 mg / cm 2 , more preferably 2 to 3 mg / cm 2 .
[0050] In the present invention, the carbon substrate is preferably carbon cloth.
[0051] In the present invention, the temperature of the reduction reaction is preferably 25°C, the time is preferably 0.5 to 2 hours, and more preferably 1 to 1.5 hours; the reduction reaction is preferably carried out at normal temperature and pressure under stirring conditions, and the stirring rate is preferably 100 to 1000 rpm, and more preferably 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm or 800 rpm.
[0052] In the present invention, the concentration of Cr(VI) in the Cr(VI)-containing wastewater is preferably 4.8-10.2 mg / L; more preferably 5-10 mg / L, further preferably 6-9 mg / L, and still more preferably 7-8 mg / L.
[0053] The present invention preferably uses a dual-chamber electrochemical polytetrafluoroethylene reactor and 800rpm magnetic stirring, the reactor has two asymmetric parts, consisting of a 105mL cathode cell and a 105mL anode cell, connected by a proton exchange membrane (Nafion117, Dupont, USA). A carbon cloth with a catalyst loading size of 2.0cm×5.0cm is used as a working electrode, RuO2 / Ti (2.0cm×2.5cm) is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode. The cathode chamber contains 90mL of simulated water sample, consisting of 56.57mg / LK2Cr2O7 (10mg / L Cr(VI)) and 0.1M CH3COOH, and the anode chamber contains only 90mL0.1M CH3COOH. All reactions are carried out at room temperature (298K).
[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0055] Example 1
[0056] 1) Ce-MOF material was prepared by hydrothermal method; 0.1954 g (0.45 mmol) Ce(NO3)2·6H2O and 0.0946 g (0.45 mmol) trimesic acid were dissolved in 25 mL ethanol, 25 mL DMF containing 0.09 mmol PVP was added, and the mixture was stirred at 800 rpm for 2 h at room temperature, and then placed in an autoclave, heated at 120°C for 12 h, and the solid was collected by filtration, then washed with ethanol and water, and dried at 60°C for 4 h to obtain a metal organic framework Ce-MOF material;
[0057] 2) Preparation of copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composites by impregnation and carbon heat treatment: 600 mg Ce-MOF was added to 50 g ethanol containing 28.31 mg Cu(NO3)2·3H2O (containing 7.5 mg Cu) and stirred at 25 °C for 0.5 h. The Cu / Ce-MOF was collected and placed in the middle of the constant temperature zone of a tubular furnace and heated at 25 mL·min. -1 In an atmosphere of high-purity nitrogen (purity of 99.99%), the temperature was raised to 950°C and maintained for 2 hours to carbonize the material. The heating rate was 5°C min -1 , and obtained a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material Cu / CeO2@C, with a copper loading of 2.4 wt%, recorded as (Cu(2.4) / CeO2@C).
[0058] Example 2
[0059] The preparation method of Ce-MOF material in this embodiment is the same as that in Embodiment 1.
[0060] Copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composites were prepared by impregnation and carbon heat treatment: 600 mg Ce-MOF was added to 50 g ethanol containing 56.63 mg Cu(NO3)2·3H2O (containing 15 mg of Cu), stirred at 25 °C for 0.5 h, and the Cu / Ce-MOF was collected and placed in the middle of the constant temperature zone of a tube furnace and heated at 25 mL min -1 In the atmosphere of high-purity nitrogen, the temperature was raised to 950 °C and maintained for 2 h to carbonize the material. The heating rate was 5 °C min -1 , and obtained the Cu / CeO2@C sample with a copper loading of 3.8wt%, recorded as Cu(3.8) / CeO2@C.
[0061] Example 3
[0062] The preparation method of Ce-MOF material in this embodiment is the same as that in Embodiment 1.
[0063] Copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composites were prepared by impregnation and carbon heat treatment: 600 mg Ce-MOF was added to 50 g ethanol containing 113.25 mg Cu(NO3)2·3H2O (containing 30 mg of Cu), stirred at 25 °C for 0.5 h, and the Cu / Ce-MOF was collected and placed in the middle of the constant temperature zone of a tube furnace at 25 mL min -1 In the atmosphere of high-purity nitrogen, the temperature was raised to 950 °C and maintained for 2 h to carbonize the material. The heating rate was 5 °C min -1 , and obtained the Cu / CeO2@C sample with a copper loading of 8.0wt%, recorded as Cu(8.0) / CeO2@C.
[0064] Example 4
[0065] The preparation method of Ce-MOF material in this embodiment is the same as that in Embodiment 1.
[0066] Copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composites were prepared by impregnation and carbon heat treatment: 600 mg Ce-MOF was added to 50 g ethanol containing 226.5 mg Cu(NO3)2·3H2O (the mass of Cu was 60 mg), stirred at 25 °C for 0.5 h, and the Cu / Ce-MOF was collected and placed in the middle of the constant temperature zone of a tube furnace and heated at 25 mL min -1 In the atmosphere of high-purity nitrogen, the temperature was raised to 950 °C and maintained for 2 h to carbonize the material. The heating rate was 5 °C min -1 , and a Cu / CeO2@C sample was obtained with a copper loading of 16.2wt%, recorded as Cu(16.2) / CeO2@C.
[0067] Example 5
[0068] The preparation method of Ce-MOF material in this embodiment is the same as that in Embodiment 1.
[0069] Copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composites were prepared by impregnation and carbon heat treatment: 600 mg Ce-MOF was added to 50 g ethanol containing 453 mg Cu(NO3)2·3H2O (containing 120 mg Cu) and stirred at 25 °C for 0.5 h. The Cu / Ce-MOF was collected and placed in the middle of the constant temperature zone of a tube furnace and heated at 25 mL min -1 In the atmosphere of high-purity nitrogen, the temperature was raised to 950 °C and maintained for 2 h to carbonize the material. The heating rate was 5 °C min -1 , and obtained a Cu / CeO2@C sample with a copper loading of 32.1wt%, recorded as Cu(32.1) / CeO2@C.
[0070] Comparative Example 1
[0071] The Ce-MOF material was prepared by a hydrothermal method; 0.1954 g (0.45 mmol) of Ce(NO3)2·6H2O and 0.0946 g (0.45 mmol) of trimesic acid were dissolved in 25 mL of ethanol, 25 mL of DMF containing 0.5 g of PVP was added, and after stirring at room temperature for 2 h, the mixture was placed in an autoclave and heated at 120°C for 12 h. The solid was collected by filtration, then washed with ethanol and water, and dried at 60°C for 4 h to obtain a metal organic framework Ce-MOF material;
[0072] Preparation of cerium oxide carbon nanorod composites by carbon thermal treatment: 600 mg Ce-MOF was added to 50 g ethanol and stirred at 25 °C for 0.5 h. The Ce-MOF was collected and placed in the middle of the constant temperature zone of a tube furnace and heated at 25 mL min -1 In an atmosphere of high-purity nitrogen (purity of 99.99%), the temperature was raised to 950°C and maintained for 2 hours to carbonize the material. The heating rate was 5°C min -1 , and obtained a Ce-MOF-derived cerium oxide carbon nanorod composite material, denoted as (CeO2@C).
[0073] Comparative Example 2
[0074] Cu-MOF was prepared by a hydrothermal method: 0.0286 g (0.45 mmol) of Cu(NO3)2·3H2O and 0.0946 g (0.45 mmol) of trimesic acid were dissolved in 25 mL of ethanol, 25 mL of DMF containing 0.5 g of PVP was added to the ethanol, and after stirring at room temperature for 2 h, the mixture was placed in an autoclave and heated at 120°C for 12 h. The solid was collected by filtration, then washed with ethanol and water, and dried at 60°C for 4 h to obtain the Cu-MOF material.
[0075] Preparation of Cu-MOF-derived octahedral composites by carbon thermal treatment: Cu-MOF was placed in the middle of the constant temperature zone of a tube furnace and heated at 25 mL min -1 In the atmosphere of high-purity nitrogen, the temperature was raised to 950 °C and maintained for 2 h to carbonize the material. The heating rate was 5 °C min -1 , a Cu-MOF-derived octahedral composite material was obtained, denoted as Cu@C.
[0076] Comparative Example 3
[0077] Cu-loaded carbon nanotube (Cu / CNT) catalyst: 600 mg of carbon nanotubes were added to 50 g of ethanol containing 226.5 mg of Cu(NO3)2·3H2O (the mass of Cu contained was 60 mg). After stirring for 0.5 h, the ethanol evaporated and the Cu / CNT sample was collected and placed in the middle of the constant temperature zone of a tube furnace. -1 In the atmosphere of high-purity nitrogen, the temperature was raised to 950 °C and maintained for 2 h to carbonize the material. The heating rate was 5 °C min -1 , a Cu / CNT sample was obtained, and the Cu content was the same as that in Example 4, namely Cu(16.2) / CNT.
[0078] Structural characterization
[0079] Figure 1 is the X-ray diffraction pattern of Cu / CeO2@C prepared in Examples 1 to 5; Figure 1 As shown, the typical peak of Cu was observed on the Cu / CeO2@C catalyst.
[0080] Figure 2 SEM images of CeO2@C in Comparative Example 1 and Cu / CeO2@C prepared in Examples 1 to 5, where (a) is CeO2@C, (b) is Cu(2.4) / CeO2@C, (c) is Cu(3.8) / CeO2@C, (d) is Cu(8.0) / CeO2@C; (e) is Cu(16.2) / CeO2@C; (f) is Cu(32.1) / CeO2@C; Figure 2It can be seen that CeO2@C shows a rod-like structure with a diameter of about 150 nm. In the absence of Cu loading, Ce(III) in Ce(NO3)3 easily reacts with H3BTC ligands to form a rod-like morphology. When the copper loading is lower than 32.1wt.%, the Cu / CeO2@C catalyst maintains the CeO2@C rod structure. However, high copper content (e.g., 32.1wt.%) causes a slight collapse of the rod-like structure.
[0081] Figure 3 TEM images of CeO2@C in Comparative Example 1 and Cu / CeO2@C prepared in Examples 1 to 5, wherein (a) is CeO2@C, (b) is Cu(2.4) / CeO2@C, (c) is Cu(3.8) / CeO2@C, (d) is Cu(8.0) / CeO2@C; (e) is Cu(16.2) / CeO2@C; (f) is Cu(32.1) / CeO2@C; Figure 3 It can be seen that the morphology of samples with different copper loadings is different. The average length of Cu(16.2) / CeO2@C is about 150nm, and the average diameter of the etched holes is about 90nm.
[0082] Figure 4 TEM images of Cu(16.2) / CeO2@C prepared in Example 4, where (a) is a 100nm TEM image, (b) and (c) are 5nm TEM images, (d) is a 500nm TEM image, (e) is a Cu element distribution image, and (f) is a Ce element distribution image. Figure 4 It can be seen that in Cu2O, the interplanar distance of (200) is 0.213nm, while for Cu(16.2) / CeO2@C, the interplanar distance of adjacent planes (111) is 0.312nm, indicating the existence of Cu2O and CeO2 and different interfaces between them that are most likely related to the Cu-[OX]-Ce structure. At the same time, the distribution of copper elements in Cu(16.2) / CeO2@C and the matching EDS element mapping image are almost the same as those of Ce elements, which is mainly due to the formation of Cu-[OX]-Ce structure.
[0083] Application Example 1
[0084] The materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were respectively used as electrocatalytic reduction catalysts for Cr(VI) in the reaction of reducing dichromate ions in an aqueous phase.
[0085] The specific method is: using the prepared catalyst as an electrocatalytic cathode, adding wastewater containing pollutants into the cathode tank, and performing an electrocatalytic reduction degradation reaction of potassium dichromate at an initial pH of 2.91 and an applied potential of -1.0V vs. SCE. The specific test is as follows:
[0086] A double-chamber electrochemical polytetrafluoroethylene reactor was used. The reactor had two asymmetric parts, consisting of a 105 mL cathode cell and a 105 mL anode cell, connected by a proton exchange membrane (Nafion 117, Dupont, USA).
[0087] A carbon cloth with a catalyst loading size of 2.0 cm × 5.0 cm was used as the working electrode (the amount of catalyst on the carbon substrate was 3 mg / cm 2 ), RuO2 / Ti (2.0cm×2.5cm) was used as the counter electrode, and saturated calomel electrode was used as the reference electrode.
[0088] The cathode chamber contained 90 mL of simulated water sample, consisting of 56.57 mg / L K2Cr2O7 (10 mg / L Cr(VI)) and 0.1 M CH3COOH, i.e., the initial Cr(VI) concentration was 10 mg / L; the anode chamber contained only 90 mL of 0.1 M CH3COOH. All reactions were carried out at room temperature (298 K).
[0089] The electrocatalytic reaction was carried out at 25°C and 800 rpm mechanical stirring, and samples were collected at 1, 3, 6, 10, 20, 40, 60, 90, and 120 minutes using a 0.22 μm aqueous needle filter. The concentrations of Cr(VI) and total chromium in the samples were determined by UV spectrophotometry and atomic absorption spectrometry, respectively.
[0090] Figure 5The reduction performance results of different materials for dichromate ions, (a) is the reduction removal curve of the materials prepared in Comparative Examples 1 to 3 and Example 4, (c) is the reduction removal curve of the materials prepared in Examples 1 to 4, (b) and (d) are the mass activities of Cu in the reaction process corresponding to (a) and (c), respectively. First, the electrocatalytic reduction effect of Cr(VI) of Comparative Examples 1 to 3 and Example 4 at an applied potential of -1.0V vs. SCE was compared. After 120 minutes of electrocatalytic reaction, a very low Cr(VI) removal rate of 20% was obtained on CeO2@C. Since there are no catalytic active sites in the CeO2@C cathode, the direct electrochemical reduction of Cr(VI) by electrons is the reason for the very low Cr(VI) removal rate on CeO2@C. In contrast, after 120 minutes of reaction, 70% of Cr(VI) was removed on Cu@C, which is much faster than on CeO2@C. This significantly enhanced Cr(VI) reduction can be reasonably attributed to the presence of Cu species (i.e., metallic Cu and Cu(I)), which are able to directly react with Cr(VI) via redox reactions, resulting in efficient Cr(VI) reduction. The redox reactions of Cu species with Cr(VI) are feasible at very low potentials for Cu / Cu(I) and Cu(I) / Cu(II) and at very high potentials for Cr(VI) / Cr(III). The Cu / CNT and Cu / CeO2@C catalysts consistently exhibited significant Cr(VI) reduction, again demonstrating the key role of Cu species in electrocatalytic Cr(VI) reduction.
[0091] Although the removal of Cr(VI) was improved in the presence of Cu, the catalytic activity of the catalysts varied with the increase of CeO2 and Cu content. To verify the role of CeO2, the electrocatalytic Cr(VI) reduction of Cu(16.2) / CeO2@C was compared with that of Cu / CNT, since the Cu loading of Cu / CNT was the same as that of Cu(16.2) / CeO2@C. After 120 min of reaction, the Cr(VI) removal efficiency of Cu(16.2) / CeO2@C was 95%, which was much higher than that of Cu / CNT (76%). Figure 5 In addition, the initial activity of Cu(16.2) / CeO2@C is 1.55min -1 mg -1 , indicating that the catalytic activity of Cu(16.2) / CeO2@C is significantly higher than that of Cu / CNT ( Figure 5 (b)). Figure 1The characterization results show that the Cu species in Cu(16.2) / CeO2@C are highly dispersed on CeO2, forming a Cu-[OX]-Ce structure through a strong Cu-CeO2 interaction, while the Cu particles are aggregated on the CNT surface, and the XRD diffraction peak of metallic Cu is very strong. Therefore, the highly dispersed Cu species in Cu(16.2) / CeO2@C can provide abundant catalytic active sites for Cr(VI) reduction, thereby enhancing the removal of Cr(VI). In addition, the catalytic activity of the Cu / CeO2@C catalyst varies with the change of Cu loading ( Figure 5 (c)). Increasing the Cu content from 2.4wt.% to 16.2wt.% resulted in an increase in the Cr(VI) removal from 58% to 95% after 120 min of reaction, while increasing the Cu content to 32.1wt.% did not result in further enhancement, which may be due to the aggregation of active sites at such a high Cu loading. Therefore, Cu(16.2) / CeO2@C exhibited the best catalytic activity with a Cr(VI) removal of 95% and a Faradaic efficiency of 26%. It is worth noting that the catalytic activity of Cu(16.2) / CeO2@C is even higher than that of Cu@C, despite the much higher copper content of 47wt.% in Cu@C. The activity normalized from the Cu mass ( Figure 5 Figure (d) provides a deeper understanding of the dependence of the catalytic activity on the Cu content. The normalized activity decreases monotonically with Cu content, and the dependence on Cu content decreases. This unique dependence can firstly be attributed to the gradual aggregation of Cu particles with increasing Cu content, resulting in a decrease in exposed Cu active sites. In addition, at the same CeO2 content, the increase in Cu content leads to the Cu-CeO2 interface and the Cu + -Ov-Ce 3+ Therefore, the dependence of the Cu content-normalized activity of the Cu / CeO2@C catalyst was reduced, which once again verified the key role of the Cu-CeO2 interface in enhancing the electrocatalytic Cr(VI) reduction.
[0092] Application Example 2
[0093] The reaction potentials in Application Example 1 were adjusted to -0.6, -0.8, -1.0 and -1.2 V vs. SCE, respectively. The Cu(16.2) / CeO2@C material in Example 4 was applied to the reduction reaction to explore the effects of different reaction potentials on the reduction and removal of dichromate. The results are shown in Figure 2. Figure 6 As shown, Figure 6 (a) is the reduction removal curve. Figure 6(b) is the mass activity of Cu in the reaction. The initial activity of the catalyst for the reduction of Cr(VI) increases regularly with the applied potential in the range of -0.6 to -1.0 V, while a further increase in potential leads to a decrease in the mass activity. The enhancement of the catalyst activity can be attributed to the enhancement of active H* radicals on the surface of metal Cu and the promotion of the formation of active H* radicals, thereby accelerating the reduction of Cr(VI). When the applied potential further increases from -1.0 V to -1.2 V, the activity of the electrocatalytic reduction of Cr(VI) decreases, which is mainly attributed to the anionic repulsion between the anionic Cr(VI) and the cathode surface and the enhancement of HER at high potentials. Therefore, on Cu(16.2) / CeO2@C, the electrocatalytic reduction activity of Cr(VI) is the highest at 1.60 min at -1.0 V. -1 mg -1 , with a Faradaic efficiency of 28.6%, showing a volcano-type dependence of the catalytic activity on the applied potential.
[0094] Application Example 3
[0095] The initial pH of the solution in Application Example 1 was adjusted to 2.91, 4.6, and 8.13, respectively. The Cu(16.2) / CeO2@C material in Example 4 was applied to the reduction reaction to explore the effect of different reaction pH values on the reduction and removal of dichromate by the material. The results are shown in Figure 7 As shown, Figure 7 (a) is the reduction removal curve. Figure 7 (b) is the mass activity of Cu in the reaction. The removal of Cr(VI) was similar at pH 2.9 and 4.6, while the reduction of Cr(VI) was significantly inhibited at pH 8.13. Considering that the reduction of Cr(VI) on the electrode surface is a heterogeneous catalytic reaction, Cr(VI) adsorption plays a crucial role as expected. The isoelectric point of Cu(16.2) / CeO2@C is approximately 5.4 (Table 1), which is conducive to the electrostatic attraction of negatively charged Cr(VI) species to the catalyst surface at pH below 5.4. In contrast, when the pH is above 5.4, deprotonation leads to a negative charge on the catalyst surface, inducing expulsion interactions with anionic Cr(VI), thereby inhibiting the adsorption and conversion of Cr(VI) on the catalyst surface. Therefore, at pH values below 4.6, the Cr(VI) conversion is higher than that at pH 8.13. The reduction rates of Cr(VI) were similar at pH 2.9 and 4.6, indicating that further increasing the acidity did not lead to a significant enhancement of Cr(VI) reduction, probably because the catalyst surface was already effectively protonated under the acidic reaction conditions.
[0096] The structural parameters of the materials of different embodiments and comparative examples are shown in Table 1.
[0097] Table 1 Structural parameters of catalysts
[0098]
[0099] Application Example 4
[0100] Under the same conditions as in Application Example 1, the material prepared in Example 4 was used as an electrode to carry out the electrocatalytic reduction of Cr(VI). After the reaction, the electrode was cleaned, recovered and reused, and this cycle was repeated 10 times. Figure 8 As shown, (a) is the reduction removal curve, and (b) is the mass activity diagram of Cu in the reaction; Figure 8 The results show that the Cr(VI) removal rate of each catalyst cycle is stable in the range of 90-94%, indicating that the material prepared in Example 4 can still maintain a high catalytic activity within 10 catalyst cycles and can be used as a stable and promising electrode for the electrocatalytic removal of Cr(VI) from water.
[0101] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Application of a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material in electrocatalytic reduction of Cr(VI), characterized in that: The method for preparing the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material is characterized by comprising the following steps: A cerium precursor, a dispersant, an organic ligand and an organic solvent are mixed and subjected to a hydrothermal reaction to obtain a Ce-MOF material; the organic ligand comprises trimesic acid; The Ce-MOF material, the copper source and the impregnation solvent are mixed and loaded to obtain the copper-loaded Ce-MOF; The copper-loaded Ce-MOF is subjected to a carbonization reaction in a protective atmosphere to obtain a copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material.
2. The use according to claim 1, characterized in that: The cerium precursor includes cerium nitrate hexahydrate or cerium trichloride heptahydrate; the molar ratio of cerium element to organic ligand in the cerium precursor is 1:1-3.
3. The use according to claim 2, characterized in that: The dispersant includes polyvinyl pyrrolidone or polyvinyl alcohol; the molar ratio of the dispersant to the cerium precursor is 1:3-6.
4. The use according to claim 3, characterized in that: The organic solvent includes at least one of ethanol and N,N-dimethylformamide; the temperature of the hydrothermal reaction is 120-140° C., and the time is 2-12 hours.
5. The use according to claim 1, characterized in that: The copper source includes copper nitrate trihydrate or copper sulfate pentahydrate; the mass ratio of the copper source to the Ce-MOF material is 4-80:100; the load temperature is 25° C., and the time is 0.5-1 h.
6. The use according to claim 5, characterized in that: The temperature of the carbonization reaction is 800-950°C, and the time is 0.5-2h; the protective gas used in the protective atmosphere is nitrogen or argon; the flow rate of the protective gas is 25-100mLmin -1 .
7. The use according to any one of claims 1 to 6, characterized in that: In the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material, the loading amount of Cu is 2.4-32.1 wt %.
8. The use according to claim 7, characterized in that: The application method comprises the following steps: after the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material is loaded on a carbon substrate, the composite material is used as a working electrode to carry out a reduction reaction on wastewater containing Cr(VI).
9. The use according to claim 8, characterized in that: The amount of the copper-loaded Ce-MOF-derived cerium oxide carbon nanorod composite material on the carbon substrate is 0.5 to 5 mg / cm 2 The concentration of Cr(VI) in the Cr(VI)-containing wastewater is 4.8-10.2 mg / L.
10. The use according to claim 8, characterized in that: The temperature of the reduction reaction is 25° C. and the time is 0.5 to 2 hours.
Citation Information
Patent Citations
Preparation method and application of organic framework supported CeO2 / CuO electrocatalytic material
CN110586193A
Preparation method of cerium dioxide loaded metal oxide nano-catalyst
CN115608354A
Metal particle Cu-loaded CeO2 catalyst for catalytic synthesis of methanol through hydrogenation of carbon dioxide as well as preparation method and application of metal particle Cu-loaded CeO2 catalyst
CN118059873A
Preparation method and application of Cu-based catalyst taking CeO2 as carrier
CN118996490A
Preparation of copper oxide-cerium oxide-supported nano-gold catalysts and its application in removal of carbon monoxide in hydrogen stream
US20130183221A1